PENGEMBANGAN SISTEM POINT OF SALE KE PEMROGRAMAN WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Hermawati -; Purwadi Budi Santoso; Din Din Jalaludin; Ahmad Sujana; Givy Devira Ramady (Politeknik Harapan Bersama Tegal, 2023)
The Point Of Sale (POS) business management system is an application program that can facilitate all trading processes, but this system can only be installed on low-spec computers with a fairly complicated installation process. Based on these problems, the authors try to find solutions on how to develop POS application programs into web programming so that they can be installed on all mainstream operating system products. The POS system developed is a management system that can manage several important functions in web-based business management using the PHP programming language with the Code Igniter 3 Framework, Apache web server and MySQL database. The research methodology used is an action research method with data collection techniques through interviews. The waterfall development model is designed using the UML design method, and tested using black box testing techniques. Through this development process, desktop-based POS application programs have been successfully developed into web programming and can be installed on mainstream operating system products such as Windows, Linux and Macintosh.